Lantbruksföretagets tillväxtstrategi och finansiella sökbeteende - Hörnstein, Anders; Joelson, Anders (2009)
The structural rationalization of the agricultural sector in Sweden has led to many expansive, professional companies orientated towards growth. The agricultural sector is a very capital-intense sector and is characterized by the need for large sums of capital in form of buildings, inventory and arable land. The capital need is especially large for companies who have an ambition of growth and development of the company in the near future.